A Spectrally Efficient Frequency Diversity Technique for Single-Carrier Modulations with Frequency Division Multiplexing - Araújo, Teresa (2018)
When the number of relevant propagation paths between the transmitter and the receiver is small and/or when they are not separable (i.e. the difference between the corresponding delays is smaller than the symbol duration), we can have deep fading effects and poor performance, especially for slow-varying channels. In this case, the use of diversity techniques is strongly recommendable. In this paper, we consider an single-carrier-based (SC) block transmission, employing frequency domain equalisation (FDE) receivers and we present a frequency diversity technique that allows high spectral efficiencies. As with conventional frequency diversity techniques, L replicas of a given signal are transmitted at L different frequencies. However, contrarily to conventional frequency diversity schemes, up to L users can share this set of L frequency bands. Since this leads to strong interference levels, we propose an iterative, frequency-domain receiver where all the users sharing the L frequencies are jointly detected. Our performance results show that the proposed frequency diversity scheme allows high diversity gains, while keeping the spectral efficiency of conventional SC schemes. Moreover, we can cope with channels that can be severely time-dispersive and/or can have deep fading effects.